ANALISIS PENGEMBANGAN POTENSI WISATA DI DESA SANGRAWAYANG - Bobi Grahadinansyah; Neng Rani Nabawiyah; Yopani Selia Almahisa; Rossa Najwa; Virya Nanda Romanista; Astri Sri Rahayu; Muhammad Galuh Sutisna; Taufik Kurnia Azis; Pratama Ginanjar Kharisman; Ta Aliyono Hadi; Ahmad khuzairi; Deden Rahmat; M. Alfirdan; Nuraiman; Zafar Akbar; Dimas Arya Pamungkas; Dera Septa; Tomi Lotama; Ade Sopian; Moch Alif Wicaksana; Anang Suryana; Samsul Pahmi; CSA Teddy Lesmana (Jurnal Pengabdian Kepada Masyarakat Abdi Putra, 2023)
Sangrawayang Village is one of the villages located in Sukabumi Regency and has a development direction as a tourist village, nowadays the development of the village into a tourist village is one alternative for local economic development. Sangrawayang village has many interesting natural resources, rich in Sundanese cultural values and religious culture which is the main focus of this research, and various historical places are found around it. In addition, Sangrawayang Village has excellent development potential when viewed from the geographical and accessibility aspects because this village is also an access road to the Geopark tourism destination area, Ciletuh. The purpose of this research is to analyze the tourism potentials that can be developed in Sangrawayang village, Sukabumi Regency. This study uses a descriptive method with a quantitative approach where primary data is obtained by conducting interviews with elders and managers as local communities and also direct observation. Meanwhile, secondary data were obtained from Sangrawayang Village, journals and also supporting books. The results obtained from this study are the discovery of the potential for the development of religious tourism, namely the Cibeas and Kwan-im cultural villages. Cibeas village is a cultural village that is thick with religious traditions such as: village celebration on 03 month 03 of 1993 which is held every year, Super Semar, and the existence of the Rabbi Mosque. Meanwhile, Kwan-im itself is a place of worship for Buddhism.